Self-perceived employability, well-being and institutional embeddedness of accounting students - Elette van den Berg; Sebastiaan Rothmann (South African Journal of Business Management)
Purpose: This study investigates the associations between financial accounting students’ self-perceived graduate employability, well-being and institutional embeddedness in a higher education institution.